Dare to lead [compact disc, unabridged] : brave work, tough conversations, whole hearts - Brown, Brené (Random House Audio, 2018)
In her number one New York Times best sellers, Brené Brown has taught what it means to dare greatly, rise strong, and brave the wilderness. Now, based on new research conducted with leaders, change makers, and culture shifters, she's showing listeners how to put those ideas into practice so they can step up and lead.